IMPACT OF POLYCYSTIC OVARY SYNDROME ON QUALITY OF LIFE OF WOMEN IN EARLY REPRODUCTIVE AGE - Pakharenko, L.V.; Kyshakevych, I.T.; Vorobii, V.D. (World of Medicine and Biology, 2018)
We studied quality of life in 60 women in early reproductive age with polycystic ovary syndrome (PCOS) who formed basic group. 30 women without this pathology were controls. Diagnosis of PCOS was based on the Rotterdam criteria. Ultrasound examination of pelvic organs, sexual steroids hormones, androgens, level of glucose, amount of insulin, lipoproteins were determined in blood serum. Quality of life was studied with help of 36-Item Short Form Health Survey. Average age of patients in basic group was 21.00±0.49 years, in control one – 21.67±0.34. All persons with PCOS had oligomenorrhea, 28.33 % – amenorrhea. Clinical signs of hyperandrogenia had 68.33 % of women in basic group. However, laboratory rise of androgens was determined only in 18.33 % of patients. We founded that increased ratio luteinizing hormone / follicle stimulating hormone more than 2.5 had 61.67 % persons with PCOS. But the amount of antimullerian hormone in blood was high in all patients in basic group. Ultrasound changes of ovarian tissue that indicate PCOS were determined in all women in basic group. 33.33 % of them had increased body mass index versus 16.67 % of controls. But the rate of other metabolical disorders such as insulin resistance, impaired glucose tolerance and lipid metabolism disorders were found only in 18.33 % of persons with PCOS. Scores of the physical component of SF-36 in women of basic group were slightly less than in controls. More pronounces decline was determined in parameters of the psychological component. Especially decrease was found in indices of scores “Vitality” on 15.16 % (p=0.04) and “Social functioning” – on 18.14 % (p=0.02) compared to healthy women. Thus, the decrease of the psychological component of quality of life is typical for patients with PCOS, especially the scores “Vitality” and “Social Functioning”.
Keywords: polycystic ovary syndrome; early reproductive age; quality of life